2018
DOI: 10.1016/j.dci.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular trap-like fiber release may not be a prominent defence response in snails: evidence from three species of freshwater gastropod molluscs

Abstract: The discovery that mammalian neutrophils generate extracellular chromatin fibers that entrap/kill bacteria supported a new paradigm for innate immunity in animals. Similar findings in other models across diverse taxa have led to the hypothesis that the phenomenon is ancient and evolutionary conserved. Here, using a variety of synthetic (e.g. peptidoglycan) and biological (e.g. trematode larvae) components to investigate extracellular trap-like (ET-like) fiber production in vitro by haemocytes of Lymnaea stagna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, there is no research on the formation of ETs in R. philippinarum. And knowledge of the functions of ETs is still limited in mollusks, mainly restricted to their antibacterial activity (Poirier et al, 2014;Ng et al, 2015;Skala et al, 2018). In the present study, the formation of ETs was first identified in the clam R. philippinarum, and also the potential mechanism of ET formation was also investigated.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, there is no research on the formation of ETs in R. philippinarum. And knowledge of the functions of ETs is still limited in mollusks, mainly restricted to their antibacterial activity (Poirier et al, 2014;Ng et al, 2015;Skala et al, 2018). In the present study, the formation of ETs was first identified in the clam R. philippinarum, and also the potential mechanism of ET formation was also investigated.…”
Section: Discussionmentioning
confidence: 81%
“…For example, the proteobacteria Escherichia coli could induce the ET formation of shrimp hemocytes, and the produced DNA fibers participated in the ET-mediated bactericidal killing (Ng et al, 2015). In snails, ET-like fibers could be induced by a variety of synthetic (e.g., peptidoglycan) and biological (e.g., trematode larvae) components (Skala et al, 2018). However, knowledge on the function of ETs is still limited in the marine mollusks so far.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of vertebrate cells such as neutrophils, mast cells, eosinophils and macrophages, have been reported to possess the ability to generate ETs (Chow et al, 2010;von Köckritz-Blickwede et al, 2008;Yousefi et al, 2008). Among invertebrates, ETs have been found in shrimp, oysters, mussels, earthworms, snails and amoebae (Homa et al, 2016;Ng et al, 2013;Poirier et al, 2014;Robb et al, 2014;Skála et al, 2018;Zhang et al, 2016). However, knowledge on the formation and antibacterial activities of hemocyte ETs is still deficient in invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…2B-E, 3C-D) (Dikkeboom et al, 1987;Adema et al, 1993). Additionally, haemocytes of L. stagnalis (and those of Planorbarius corneus and Radix lagotis snails) have recently been shown to generate extracellular trap-like (ET-like) fibers in vitro (Skála et al, 2018). Despite the fact that the functional characterisation of the fibers in the snail defence is required, these structures produced by, for example, neutrophils (neutrophil extracellular traps) of vertebrates or haemocytes (ET-like fibers) of invertebrates including molluscs are considered to facilitate elimination of bacteria and eukaryotic unicellular/multicellular parasites in the extracellular milieu (Hermosilla et al, 2014;Robb et al, 2014;Poirier et al, 2014;Lange et al, 2017).…”
Section: The Internal Defence System Of Uninfected L Stagnalis Is Onmentioning
confidence: 99%